HIV among People Who Inject Drugs in the Middle East and North Africa : Systematic Review and Data Synthesis - Mumtaz, Ghina R.; Weiss, Helen A.; Thomas, Sara L.; Riome, Suzanne; Setayesh, Hamidreza (Public Library of Science, 2015)
It is perceived that little is known about the epidemiology of HIV infection among people who inject drugs (PWID) in the Middle East and North Africa (MENA). The primary objective of this study was to assess the status of the HIV epidemic among PWID in MENA by describing HIV prevalence and incidence. Secondary objectives were to describe the risk behavior environment and the HIV epidemic potential among PWID, and to estimate the prevalence of injecting drug use in MENA.